Differential response patterns of soil fungal and bacterial communities to typical vegetation types in the Yellow River floodplain ecosystem - Jinyong Gao; Binghai Lei; Qianyun Yu; Yaru Nie; Anwei Su; Mingli Zang; Shengyao Cai; Wenwen Zhang; Tingting Fang; Yanyan Yu (Journal of Freshwater Ecology)
Soil microorganisms are one of the primary driving factors of biogeochemical cycles in floodplain ecosystems. Vegetation type has an impact on the activities of soil microorganisms. However, it is currently unclear whether the composition and structure of soil bacterial and fungal communities in floodplain ecosystems have a consistent response pattern to vegetation communities. In this research, Illumina Mi-Seq sequencing technology was employed to study the soil fungal and bacterial communities covered by three typical vegetation communities in the Yellow River floodplain ecosystem. Our results showed that the underground biomass, total carbon (TC) and nitrogen (TN) were significantly different between the three vegetation communities. In the surface soil of summer, the Shannon index of fungi community was the highest in Tamarix chinensis (T. chinensis) and the lowest in Phragmites australis (P.australis). In autumn, the Shannon and Simpson indices of bacterial communities in surface soil were the highest in the P.australis and the lowest in the Sonchus arvensis (S.arvensis), but there was no significant difference in the β-diversity of bacterial community among the three vegetation communities. In autumn, the Chao1 index of fungal community in subsoil was the highest in P.australis and the lowest in S.arvensis, while there was no significant difference in the α-diversity of bacterial community among the three vegetation communities. In addition, there were considerable disparities in the fungal and bacteria community structure in various vegetation soils. Redundancy analysis (RDA analysis) showed that TN, TC, AP, pH, NO3-, NH4+ and moisture content were key factors driving bacterial community structure, while TP, NH4+, pH and moisture content were essential factors driving fungal community composition. These outcomes help to improve our understanding of the ecological model of soil fungal and bacterial community in floodplain ecosystems and give assistance in improving the role of an ecological barrier and floodplain service possibilities.